PENGARUH STRUKTUR MODAL, PROFITABILITAS, KEPUTUSAN HEDGING DAN KEPEMILIKAN MANAJERIAL TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SEKTOR PERTAMBANGAN YANG TERDAFTAR PADA BURSA EFEK INDONESIA - Eka Nuraini Rachmawati; Randi Saputra; Hasiholan Serasi Sinamo (UIR Press, 2023)
This study aims to analyze the effect between capital structure, profitability, hedging decisions and managerial ownership of firm value. The population in this study are mining companies listed on the Indonesia Stock Exchange for the 2016-2021 period. By using purposive sampling technique, the final sample used was 41 companies. The type of data used is secondary data obtained from the company's annual report on the Indonesia Stock Exchange. The data analysis technique in this study used multiple regression analysis with the EVIEWS 10 application tool. The results showed that all independent variables simultaneously affected firm value. Partially the variables of capital structure, hedging decisions and managerial ownership do not have a significant effect on firm value while profitability has a significant effect on firm value.